Analysis of flexibility in humanoid robot structure design to attain human-like motions / Hanafiah Yussof … [et al.] - Yussof, Hanafiah (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2009)
This paper presents analyses of flexibility in humanoid robot structure design focusing on design parameters of degree of freedoms and joint angle range characteristic to identify elements that provide flexibility for humanoid robots to attain human-like motion. Description and correlation of physical structure flexibility between human and humanoid robot to perform motion is presented to clarify the elements. This analysis utilized the joint structure design, configuration of degree of freedoms and joint rotation range of a 21-dof humanoid robot Bonten-Maru II. Experiments utilizing this robot were conducted, with results indicates effective design parameters to attain flexibility in human-like motion.